Teachers’ Perspectives on Seating Arrangements for English Language Learners - Saputra, Muhammad Ari; Ibrahim, Akbar; Lubis, Asmaul Husna; Khairani, Nikmah (Indonesian Journal of Integrated English Language Teaching, 2025)
Students’ learning quality in the classroom is influenced by the learning environment. The ability of teachers to control the seating arrangement is required. This study sought to understand how English teachers saw setting arrangements and what challenges they encountered while implementing them. A descriptive study using a qualitative methodology was used in this investigation. The study’s findings showed how crucial the English teacher’s opinion of the seating arrangement pattern is. The class arrangement that has been used is a separate table for solitary work and a seating pattern. In an effort to make learning enjoyable and not boring. One of the challenges that teachers frequently encountered was the state of the students, who frequently made noise when the sitting arrangement was altered. They were not only difficult to control, but they also objected to the change; b) The classroom’s tight space also makes it difficult to implement the seating arrangement plan. In order to improve the quality of learning for students, this research study aims to motivate teachers to design the learning environment.